1989
DOI: 10.1172/jci113936
|View full text |Cite
|
Sign up to set email alerts
|

Common acute lymphoblastic leukemia antigen expressed on leukemia and melanoma cell lines has neutral endopeptidase activity.

Abstract: We have previously reported that the amino acid sequence of the common acute lymphoblastic leukemia antigen (CALLA, CD10) translated from a normal human kidney cDNA clone is identical to that of neutral endopeptidase (NEP, EC 3.4.24.11). In this study, we show that by flow cytometry, a monoclonal antibody (135A3) produced against rabbit NEP reacted selectively with leukemia and melanoma cell lines expressing CALLA on their surface. A glycoprotein of apparent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 47 publications
2
24
0
1
Order By: Relevance
“…Binding of iodine-125-or tritium-labeled Ang II or hllA by the anti-Ang II mAbs or a control mAb (CDV 135) specific for neutral endopeptidase 33 was tested by liquid-phase radioimmunoassay (RIA) as previously described. 31 Briefly, the radiolabeled ligand in 20 jtl phosphate-buffered saline containing 0.1% bovine serum albumin (PBS-BSA) was reacted for 1 hour at room temperature with 20 fi\ of 1:10 diluted hybridoma supernatant in the absence or the presence of hllA or Ang II.…”
Section: Binding To Anti-angiotensin II Monoclonal Antibodiesmentioning
confidence: 99%
“…Binding of iodine-125-or tritium-labeled Ang II or hllA by the anti-Ang II mAbs or a control mAb (CDV 135) specific for neutral endopeptidase 33 was tested by liquid-phase radioimmunoassay (RIA) as previously described. 31 Briefly, the radiolabeled ligand in 20 jtl phosphate-buffered saline containing 0.1% bovine serum albumin (PBS-BSA) was reacted for 1 hour at room temperature with 20 fi\ of 1:10 diluted hybridoma supernatant in the absence or the presence of hllA or Ang II.…”
Section: Binding To Anti-angiotensin II Monoclonal Antibodiesmentioning
confidence: 99%
“…CD10 is a cell surface glycoprotein expressed in both normal and neoplastic cells, including follicular lymphoma 10) , renal cell carcinoma 11) , endometrial stromal sarcoma 11)12) , atypical fibroxanthoma 13) , and many benign or malignant tumors 11)13) , although the precise function of CD 10 in each tumor is still not fully understood 14) . CD10 expression in MM was first described by 9 Jongeneel et al 15) using flow cytometry in cell lines. Carrel et al 16)17) then showed CD10 expression in vivo in MM tissues by IHC; several other reports have significantly correlated CD10 expression levels with tumor progression 6)8) [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to those with receptor or ligand functions, others have been found to be membrane enzymes that may have important regulatory functions during B-cell maturation (1). For example, the human B-cell antigens CD10, CD45, and CD73 are enzymes possessing neutral endopeptidase, protein-tyrosine-phosphatase, and ecto-5'-nucleotidase activities, respectively (2)(3)(4). Most of the known B-cell markers are expressed during early or middle stages of B-cell ontogeny.…”
mentioning
confidence: 99%